Physicochemical, Antioxidant and Anticancer Characteristics of Seed Oil from Three Chenopodium quinoa Genotypes - Yingbin Shen; Liyou Zheng; Yao Peng; Xucheng Zhu; Fu Liu; Xinquan Yang; Haimei Li (Molecules, 2022)
Chenopodium quinoa Willd. is recognized to be an excellent nutrient with high nutritional content. However, few genotypes of quinoa were analyzed, so we found a knowledge gap in the comparison of quinoa seeds of different genotypes. This study aims to compare the physicochemical, antioxidant, and anticancer properties of seed oil from three C. quinoa genotypes. Seeds of three genotypes (white, red, and black) were extracted with hexane and compared in this study. The oil yields of these quinoa seeds were 5.68–6.19% which contained predominantly polyunsaturated fatty acids (82.78–85.52%). The total tocopherol content ranged from 117.29 to 156.67 mg/kg and mainly consisted of γ-tocopherol. Total phytosterols in the three oils ranged from 9.4 to 12.2 g/kg. Black quinoa seed oil had the highest phytosterols followed by red and white quinoas. The chemical profile of quinoa seed oils paralleled by their antioxidant and anticancer activities in vitro was positively correlated with the seed coat color. Black quinoa seed oil had the best antioxidant and anti-proliferation effect on HCT 116 cells by the induction of apoptosis in a dose-dependent manner, which may play more significant roles in the chemoprevention of cancer and other diseases related to oxidative stress as a source of functional foods.